(untitled) (Biological Sciences - PJSIR, 2002)
Fulleli canal takes off from left bank of river Indus at Kotri barrage and passes through Hydetabad city, where untreated and partially treated city sewage is added. Five samples from sewage and seven samples along Fuleli canal were collected for three years at an interval of 4 to 6 weeks. These samples were analysed for nitrogen (organic, ammonia, nitrite, nitrate) and phosphorou s (ortho, conden sed and total phosphate). The variation in the concentration of total nitrogen ranged from 22.6 to 99.2 mg L- 1 and 4.4 to 42.8 mg L- 1 and phosphorous ranged 2.6 to 44 . 1 mg L-1 and 0.041 to 15.94 mg L- 1 in sewage and along Fuleli canal respectively. The amount of nitrogen and phosphorou s added to Fuleli canal from sewage water were calculated to 316.2 and 85.3 tons/month .